Android Data Exfiltration: A Case Study - Leone, Pedro A. K.; Blaudt, Pedro O. F.; Cardinot, Ygor de A.; Lazarin, Nilson M. (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2022: Companion Proceedings of the 18th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi_estendido.2022.222773, 2022)
Our smartphones contain a lot of private and important data in it, such as family albums, bank information, passwords, documents, among others. This paper presents a survey with smartphone users, about your behavior and sense of security. Moreover, an analysis of the Android security system and were try some antivirus apps available on Google Play Store against a malware developed to steal pictures of user gallery.